2022
DOI: 10.1108/ejim-08-2021-0431
|View full text |Cite
|
Sign up to set email alerts
|

Distributed innovation, digital entrepreneurial opportunity, IT-enabled capabilities, and enterprises' digital innovation performance: a moderated mediating model

Abstract: PurposeAs an important driving factor of digital innovation, distributed innovation has received extensive attention from academia and business circles in recent years. However, extant works lack a discussion on the influence of distributed innovation on digital innovation performance. Drawing on the opportunity perspective, the study constructs a moderated mediating model to address how distributed innovation directly affects enterprises' digital innovation performance. Particularly, it investigates the moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Fourth, in the existing scholarship, MEC mediates the association between CSR activities and green innovation performance. So, more scholarships can analyze this linkage with the presence of mediating variables such as green knowledge sharing or entrepreneurial opportunities ( Boadu et al, 2021a ; Tang et al, 2022 ) to further advance our understanding of the issue. Furthermore, the sample of the current scholarship is limited to particular sectors (i.e., manufacturing and service) of the Chinese economy; the validity of the model may be affected by social and cultural factors.…”
Section: Discussion Implications and Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, in the existing scholarship, MEC mediates the association between CSR activities and green innovation performance. So, more scholarships can analyze this linkage with the presence of mediating variables such as green knowledge sharing or entrepreneurial opportunities ( Boadu et al, 2021a ; Tang et al, 2022 ) to further advance our understanding of the issue. Furthermore, the sample of the current scholarship is limited to particular sectors (i.e., manufacturing and service) of the Chinese economy; the validity of the model may be affected by social and cultural factors.…”
Section: Discussion Implications and Limitationmentioning
confidence: 99%
“…Finally, we control for financial subsidy, which has the potential to influence GIP. Extant scholarships have proved that it may be linked with enterprise innovative performance ( Boadu et al, 2021a ; Tang et al, 2022 ; Xie et al, 2022a , b ). Enterprises were asked to indicate the financial subsidy that they obtain from authorities.…”
Section: Methodsmentioning
confidence: 99%
“…The three-factor model considers the influencing factors like expertise, creative skills, and intrinsic motivation ( Amabile, 1988 ), and Woodman proposed an interaction model that suggests the interaction of individual-, team-, and organizational-levels factors affect creativity ( Woodman et al, 1993 ). Regarding digital creativity, some scholars have found that individual-level influencing factors include professional skills, digital tendency ( Lee et al, 2013 ), ambidextrous learning capabilities and digital knowledge ( Shao et al, 2021 ), digital entrepreneurial opportunity, and IT (information technology) capabilities ( Tang et al, 2022 ), team-level factors have team cognitive states, and digital project-specific cognitions ( Hadjielias et al, 2021 ). Organizational level predictors comprise the digital environment ( Lee et al, 2013 ), task variety ( Shao et al, 2021 ), organizational readiness, digital capabilities and digital organizational culture ( Zhen et al, 2021 ), orchestration, and coordinate mechanisms ( Urbinati et al, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There is considerable literature on the positive correlation between organizations having digital capability or having the ability to apply digital technology and business performance, innovation capability, and so on (Tang et al, 2022;Tumbas et al, 2018). This is because the impact of digital technology in the context of digital economy has forced all companies to make a corresponding digital shift.…”
Section: The Mediating Role Of Digital Capabilitymentioning
confidence: 99%